2007
DOI: 10.2135/cropsci2006.12.0784
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Freeze Tolerance of Zoysiagrasses: II. Carbohydrate and Proline Accumulation

Abstract: Cold hardiness among zoysiagrass (Zoysia spp.) genotypes varies, but the physiological basis for cold hardiness is not completely understood. The objective of this study was to determine the relationship of carbohydrate (starch, total soluble sugars, total reducing sugars, sucrose, glucose, and raffinose family oligosaccharides) and proline concentrations with the cold acclimation of zoysiagrass and the lethal temperature killing 50% of the plants (LT50). Thirteen genotypes of zoysiagrass were selected with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 46 publications
10
84
1
8
Order By: Relevance
“…In this study, the concentration of proline and soluble sugar were increased in shoots under low temperature, and the increase in resistant variety was significantly higher than sensitive variety. Similar results were also found in previous researches (Kushad and Yelenosky, 1987;Patton et al, 2007;Burbulis et al, 2011;Li et al, 2013). Carbohydrate and protein metabolism is the foundation for the rapeseed seedling establishment (Patton et al, 2007;Lutz, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, the concentration of proline and soluble sugar were increased in shoots under low temperature, and the increase in resistant variety was significantly higher than sensitive variety. Similar results were also found in previous researches (Kushad and Yelenosky, 1987;Patton et al, 2007;Burbulis et al, 2011;Li et al, 2013). Carbohydrate and protein metabolism is the foundation for the rapeseed seedling establishment (Patton et al, 2007;Lutz, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were also found in previous researches (Kushad and Yelenosky, 1987;Patton et al, 2007;Burbulis et al, 2011;Li et al, 2013). Carbohydrate and protein metabolism is the foundation for the rapeseed seedling establishment (Patton et al, 2007;Lutz, 2010). Transcriptome results revealed that beta-amylase and betaglucosidase genes expression were up-regulated in low temperature stress to increase the sugar content.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Pro content was determined using the ninhydrin method with slight modification (Patton et al, 2007). Seven 5 cm-long shoot segments collected from each cultivar were immediately frozen in liquid N 2 , ground using a mixer mill with grinding jars and balls (TissueLyser II; Qiagen, Dusseldorf, Germany) for 1 min, and stored as powder at −80°C until use.…”
Section: Pro Analysismentioning
confidence: 99%
“…They are usually accumulated at low temperatures, leading to improvement in plants' tolerance to cold. [3][4][5][6] Recent studies have also shown that sugar signaling is closely associated with hormone signaling, the control of growth and development, and responses to stress in plants. 7,8) Large numbers of genes are involved in sugar accumulation and can be regulated in complex ways.…”
Section: Detection Of Sugar Accumulation and Expression Levels Of Cormentioning
confidence: 99%